PERAN PRODUK MANAGER DALAM PENGEMBANGAN APLIKASI SI CANTIK - Novinda Serikandi; Mawar Mawar; Ainaya Nazilatul Fathinia Muqaffa; Revindra Al Ghivary (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2022)
Si Cantik stands for Integrated Licensing Service Application for the Public in the form of a cloud system that can be used by government agencies for free. Si Cantik itself is a web-based application that is integrated with online single submission (OSS) for licensing and non-licensing carried out by the government's One Stop Service (PTSP), both at the central and regional levels. This application was developed to facilitate transparent, effective and efficient licensing services. Product Manager or product management is a strategic function within a company organization that deals directly with matters related to product development, business improvement, product launches, to determining the marketing strategy of a product in the company. Product manager is concerned with product development. Therefore, a product manager is needed to develop the Si Cantik application. This type of research is a qualitative research with a descriptive approach, as well as data collection techniques with literature or literature studies. Si Cantik is designed to handle licensing and non-licensing processes, from the application stage to document issuance, and integrated executive report generation. The role of the product manager will help in developing the Si Cantik application. The product manager will use 12 tools to make his job easier. These 12 tools will be used for the development of the Si Cantik application and also add features that will provide convenience and convenience of service for the community.